Modernizing Agriculture: The Evolution of a Multipurpose Farm Machine - D.B. Shelke (International Journal of Advanced Robotics and Automation Technology, 2024)
In India, a nation reliant on agriculture, 70% of the population makes their living from farming. However, we can see that as the population grows, the farm is divided up among the individuals; as a result, Indian farmers often own just two acres of land. Farmers also practice traditional farming since they are extremely poor and cannot afford to buy tractors or other expensive equipment. In general, bullocks, horses, and he-buffaloes are also used by many Indian farmers for agricultural purposes. Compared to other economies, this will not meet the energy needs of the farming industry. As a result, we have created a machine that uses many different kinds of mechanisms to carry out several tasks, saving small-scale farmers time and money by cutting out the need for manual and animal labor. We employed the water sprayer, leveling attachment, seed sowing attachment, and plowing rod in this equipment. It is used in small-scale farming to carry out tasks, including field leveling, water spraying, seed sowing, and plowing. This equipment has the extra benefit of a manual drive for operation. With the aforementioned accessories, one might finish a variety of farming tasks faster, cheaper, and with less labor resources.
Keywords: Kolapani yantra; fertilizer spraying; grass cutting; leveling attachment; seed sowing; water feeding